Factors that have shaped the eEvolution of bilateral trade between Canada and Colombia in the long run (1953-2003) (2010)
Currently bilateral trade between Canada and Colombia is low. In 2003, this trade amounted to US $489 million, with Colombian imports from Canada totaling US $ 213 million (DOTS, 2004). Canada supplied approximately 4.0% of Colombia’s total trade (total imports and total exports), in contrast Colombia supplied only around 0.1% of the Canadian total trade. In 2005, Colombia was the third largest Canadian partner in South America after Brazil and Venezuela. The objective of this paper is to analyze the trade performance between Canada and Colombia using a modified gravity equation to identify the most relevant historical factors that have shaped the evolution of this bilateral trade in the long run (during the period from 1953 to 2003). The analysis includes traditional economic variables (such as population and income of the importing and exporting countries). In order to understand the qualitative nature of the evolution of this bilateral trade the second objective is to review the evolving nature of trade including commodity composition and trade characteristics.